Adaptation and Implementation of an Intervention Programme on Spanish Carers and Adolescent Patients With an Eating Disorder: Study Protocol of a Randomized Controlled Trial - Quiles, Yolanda; Quiles, María José; León, Eva María; Roncero, María; Ruiz, Álvaro; España, Maite; Romero, Cristina; Elvira, Vicente (Frontiers in Psychology, 2021)
Introduction: Interventions that may optimise the outcome during and following inpatient or day-patient treatment are needed in eating disorders, and to this end, the ECHOMANTRA programme has been developed. ECHOMANTRA is based on interventions for carers (Experienced Carers Helping Others, ECHO) and patients (Maudsley Model of Anorexia Nervosa Treatment for Adults, MANTRA) and is developed from the cognitive interpersonal model of anorexia (Schmidt & Treasure, 2006; Treasure & Schmidt, 2013). The aim of this study is to describe the study protocol of a randomised controlled trial (RCT) aimed at evaluating the efficacy of an adaptation of a novel intervention for patients and carers (ECHOMANTRA) as an add-on to treatment-as-usual. Method: In a multi‐centre pilot RCT, 80 female adolescent patients with a DSM-5 diagnosis of an ED and their carers will be randomised to receive either the ECHOMANTRA intervention as an add-on to treatment-as-usual (TAU) or TAU alone. A repeated measures design will be conducted across 4 time points. The primary outcome is patient psychological well-being and eating disorder symptoms; and secondary outcomes include body mass index, obsessive-compulsive symptoms, perfectionism, motivation to change, psychosocial adjustment and number of days in hospital or day centre. For relatives, outcome variables include psychological well-being, expressed emotion, accommodation and enabling behaviours, burden, and care skills. Discussion: The results from this trial will establish the effectiveness of ECHOMANTRA and may reveal whether and to what extent this novel intervention can optimize outcomes after inpatient treatment.